An infant with a mild SARS-CoV-2 infection detected only by anal swabs: a case report - Li,Juan (2020)
ABSTRACT Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan, China and has spread rapidly worldwide. We present a mild SARS-CoV-2 infection in a baby with non-productive cough and normal chest computed tomography, in whom only anal swabs tested positive by real-time PCR testing for SARS-CoV-2. She was given atomization inhalation therapy with recombinant human interferon alfa-1b for 10 days. Her anal swabs remained positive for eight days, whereas her throat swabs were persistently negative by real-time PCR testing. Mild and asymptomatic cases, especially in children, might present with PCR negative pharyngeal/nasal swabs and PCR positive anal swabs. Those patients are potential sources of infection via fecal-oral transmission for COVID-19.